Ancient olive presses and oil production in Cyrenaica (North-East Libya) - Buzaian, Ahmed (The British Institute for Libyan and Northern African Studies, 2022)
A comprehensive overview of Olive oil production in Cyrenaica in the Roman period, to demonstrate its economic importance within the Roman Empire.